Evaluasi Kualitas Fisik Enkapsulasi Ekstrak Daun Sirih (Piper bettle linn) Metode Destilasi Uap sebagai Feed Additive untuk Ternak Unggas - Putri, Fitria Tridyana; Haryuni, Nining (Universitas Islam Kadiri, 2025)
This study aims to determine the physical quality of encapsulated Piper bettle linn extract as a feed additive for poultry. This study is a descriptive experimental study, where this study describes the characteristics of the encapsulated product of Piper bettle linn extract steam distillation method. The results showed that the encapsulated betel leaf extract has an off-white color, a fresh aroma typical of Piper bettle linn and is crystalline. The results of the density test obtained a specific gravity of 0.74 kg/m3, a specific surface area of 42.50 mm2/g, flow rate of 5.00 g/sec and material stack angle of 24.230. Based on the study, it was concluded that the encapsulated betel leaf extract has good quality and is suitable for use as a feed additive for poultry.